1995
DOI: 10.1152/jappl.1995.79.4.1134
|View full text |Cite
|
Sign up to set email alerts
|

Gas exchange, blood lactate, and plasma catecholamines during incremental exercise in hypoxia and normoxia

Abstract: The interrelationships among blood lactate (La-) and plasma norepinephrine (NE) and epinephrine (Epi) were studied simultaneously with measures of ventilation (VE) and gas exchange during incremental exercise to exhaustion in nine healthy young men. We wanted to observe whether the tight coupling that exists during normoxic exercise between the concentrations of La- ([La-]) and of both NE and Epi would also be found in hypoxia (inspired O2 fraction = 0.14). In addition, we used recently advocated methods of V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
51
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 0 publications
15
51
1
Order By: Relevance
“…On the basis of previous findings (17,38), a WR corresponding to ϳ80% of the V O2 at L was expected to still reside in the moderate-intensity domain when performed in Hypo; this was confirmed in the present study by the identical estimated steadystate V O2p values observed in normoxia and hypoxia (without previous Hvy) and, thus, the absence of a V O2p slow component under hypoxic conditions. Thus, after the ramp incremental test and on separate days, subjects completed three repetitions of each of three different exercise protocols (Fig.…”
Section: Participantssupporting
confidence: 90%
“…On the basis of previous findings (17,38), a WR corresponding to ϳ80% of the V O2 at L was expected to still reside in the moderate-intensity domain when performed in Hypo; this was confirmed in the present study by the identical estimated steadystate V O2p values observed in normoxia and hypoxia (without previous Hvy) and, thus, the absence of a V O2p slow component under hypoxic conditions. Thus, after the ramp incremental test and on separate days, subjects completed three repetitions of each of three different exercise protocols (Fig.…”
Section: Participantssupporting
confidence: 90%
“…These relationships may be explained by our observations, as well as those of others [2,5,6], that under hypoxic conditions the LT occurred at a lower exercise intensity compared to that seen during normoxia. It is generally believed that during hypoxia there is greater sympathetic nervous system activation, which stimulates glycogenolysis and glycolysis, thus contributing to increased lactate accumulation [4,5,7,8].…”
supporting
confidence: 84%
“…Furthermore, when graded exercise is performed under hypoxic conditions, the LT is shifted leftward and occurs at a lower absolute intensity than what is observed under normoxia [2,4,5]. Whether there would be a similar shift in the onset of muscle deoxygenation (OMD) under hypoxia is unknown; thus we have undertaken this study.…”
mentioning
confidence: 95%
“…Each participant performed the same amount of work on each of the 3 days of cycling. For each individual, the relative intensity was determined from the relationship between V O2 and power output obtained during a progressive cycle test (41). The progressive cycle test was performed ϳ4 wk prior to the short-term training sessions.…”
Section: Experimental Conditionsmentioning
confidence: 99%
“…The V O2peak was assessed during the progressive exercise test to fatigue by a protocol previously used in our laboratory (41). Ventilation and gas exchange were measured continuously through the test by previously published methods (42).…”
Section: Experimental Conditionsmentioning
confidence: 99%